Pengaruh Kepemimpinan Instruksional, Iklim Sekolah dan Motivasi Kerja terhadap Kinerja Guru MIS Se-Kecamatan Rantau Utara di Kabupaten Labuhanbatu - Risanna Ritonga; Salim Aktar; Faisal Rahman Dongoran (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2023)
This study aims to determine the direct effect of: (1) instructional leadership on the work motivation of MIS teachers in North Labuhanbatu Regency; (2) school climate on the work motivation of MIS teachers in North Labuhanbatu Regency; (3) instructional leadership on the performance of MIS teachers in North Labuhanbatu Regency; (4) school climate on the performance of MIS teachers in North Labuhanbatu Regency and (5) work motivation on the performance of MIS teachers in North Labuhanbatu Regency. The research subjects were MIS teachers in North Labuhanbatu Regency with a total sample of 71 people. Sampling was done by total sampling. The research method is path analysis which aims to test the theory and obtain information about the research. Based on hypothesis testing, it can be concluded that there is a significant direct effect between: (1) instructional leadership on the work motivation of MIS teachers in North Labuhanbatu Regency of 0.245; (2) school climate on the work motivation of MIS teachers in North Labuhanbatu Regency is 0.255; (3) instructional leadership on the performance of MIS teachers in North Labuhanbatu Regency is 0.259; (4) school climate on the performance of MIS teachers in North Labuhanbatu Regency is 0.189 and (5) work motivation on the performance of MIS teachers in North Labuhanbatu Regency is 0.250. The results of the study provide an overview of instructional leadership, school climate and work motivation on teacher performance by 20.8% and the rest are determined by other factors not examined.